Correlates of sexual satisfaction among Iranians women attending South Tehran health centers: A cross-sectional study - Zeinab Tavakol; Seyedeh Tahereh Mirmolaei; Asieh Mansouri; Zohreh Momeni-Movahed; Hamid Salehiniya (Journal of Analytical Research in Clinical Medicine, 2014)
Introduction: Sexual activity not only is a crucial physiologic need, but also it has been associated with religious, mystical, and historical concepts. The aim of this study was to assess Iranian women’s sexual satisfaction and its correlating factors. Methods: This was a cross-sectional study at South Tehran health centers (STHCs), which were affiliated to Tehran University of Medical Sciences (Tehran, Iran). A convenience sample consist of 405 women who were married, had at least sixth-grade literacy level, were not addicted to opioids or alcohol, had no history of infertility, psychiatric, and physical disorders, and referred to STHCs to receive Primary Health Care services. Main outcome measures were women’s demographics, sexual function, and sexual satisfaction were assessed by a questionnaire. Results: Most women (58.2%) had moderate sexual satisfaction. A significant direct association was shown between sexual satisfaction and couple’s educational level (P < 0.001), partner’s higher income (P = 0.037), regular menstruation (P = 0.005), and degree of woman’s love toward her partner (P < 0.001). There was a significant indirect association between sexual satisfaction and gravidity number (P = 0.029), and number of offspring (P = 0.006). Having sexual intercourse at least once a week (P = 0.003), equal sex request (P = 0.028), accepting partner’s request pleasingly (P < 0.001), experiencing sexual arousal (P < 0.001), and lubrication (P < 0.001) was directly associated with sexual satisfaction. Dyspareunia (P < 0.001) and difficulty to reach orgasm (P < 0.001) showed significant indirect association. Conclusion: Women sexual satisfaction associates with interpersonal and sexual factors. Creating opportunity for midwives in health centers to consult with couples, assess their quality of sexual function, educate them, and refer them to specialists if needed, is strongly recommended for healthcare systems of Iran.